2009
DOI: 10.1088/0256-307x/26/6/060506
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of a Logistic Map Driven by White Noise

Abstract: In the real world, every nonlinear system is inevitably affected by noise. As an example, a logistic map driven by white noise is studied. Unlike previous studies which focused on the behavior under local parameters to find analytical results, we investigate the whole driven logistic map. For a white noise driven logistic map, its nondivergent interval decreases with increasing white noise. The white noise does not change the equilibrium point and two-cycle intervals in statistics, if the driven logistic map i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Zheng at al. 20 suggested that it is only after the four-cycle begins when noise can excite chaos. Figure 1(b) shows the return maps for the logistic map for a parameter value of 3.6.…”
Section: Analysis Of Noisy Logistic Mapmentioning
confidence: 99%
See 3 more Smart Citations
“…Zheng at al. 20 suggested that it is only after the four-cycle begins when noise can excite chaos. Figure 1(b) shows the return maps for the logistic map for a parameter value of 3.6.…”
Section: Analysis Of Noisy Logistic Mapmentioning
confidence: 99%
“…It hides the local dynamical changes and the higher periodic orbits. As four different periods are visible when a very low level of noise is added, this level of noise may induce chaos 20 .…”
Section: Analysis Of Nnd Model For Si Enginesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are little literatures in the study of second kind of error causation. Our previous research showed that the forecasting accuracy can be improved more than 0.3% ~ 1% by a better SNR of the input data for the forecasting of short term expressway traffic flows and wind speeds [9][10][11].…”
Section: Imentioning
confidence: 99%